1971
DOI: 10.1139/b71-154
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and classification of mycorrhizae of Douglas fir. II. Pseudotsuga menziesii + Rhizopogon vinicolor

Abstract: A common tuberculate ectomycorrhiza of Douglas fir in the Pacific Northwest, described earlier by Trappe, is further examined and defined. Tubercles consist of an outer rind of aseptate, amber, thick-walled hyphae encasing tightly packed inner elements mantled with septate, hyaline, thin-walled hyphae. Reported as a Phycomycete and a Basidiomycete, respectively, the two hyphal forms actually belong to a single fungus, Rhizopogon vinicolor A. H. Smith; cultural characteristics of this fungus are described. Pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
2

Year Published

1972
1972
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 0 publications
3
38
0
2
Order By: Relevance
“…Rhizopogon vinicolor and R. parksii produced ectomycorrhizas with mostly single monopodial to pinnate morphology, but the tuberculate morphology, a type frequently seen on field material (Zak, 1971 ;Massicotte et al, 1992 ;Goodman, 1996) was absent. Rhizopogon subcaerulescens -Douglas-fir ectomycorrhizas were of a monopodial morphology.…”
Section: mentioning
confidence: 92%
“…Rhizopogon vinicolor and R. parksii produced ectomycorrhizas with mostly single monopodial to pinnate morphology, but the tuberculate morphology, a type frequently seen on field material (Zak, 1971 ;Massicotte et al, 1992 ;Goodman, 1996) was absent. Rhizopogon subcaerulescens -Douglas-fir ectomycorrhizas were of a monopodial morphology.…”
Section: mentioning
confidence: 92%
“…In Pacific Northwest forests dominated by Pseudotsuga menziesii (Douglas fir), several section Villosuli species occur on seedlings as well as on young and ancient trees (Trappe, 1965 ;Zak, 1971 ;Alvarez & Linderman, 1983 ;Castellano, 1987 ;Borchers & Perry, 1990 ;Massicotte et al, 1992Massicotte et al, , 1994Miller et al, 1992 ;Smith et al, 1995). Several section Villosuli species also co-occur with Pseudotsuga menziesii in exotic plantations in Europe (Gross et al, 1980 ;Jansen & de Vries, 1989 ;Parlade!…”
Section: mentioning
confidence: 99%
“…This feature, along with the characteristic yellow colour, makes the species readily identifiable in field collections. Other Rhizopogon species have induced tuberculate (Zak, 1971) or coralloid (Agerer et al, 1996) ectomycorrhizas, and many other fungal genera induce tuberculate clusters on a variety of hosts (Massicotte et al, 1992).…”
Section: mentioning
confidence: 99%
“…The mature tuberculate mycorrhiza of Eucalyptus pilularis resembles in general morphology a tuberculate mycorrhiza formed in an association between Rhizopogon and Douglas fir (Zak, 1971). There are some differences, however, in the arrangement of the roots and structure of the internal rhizomorphs.…”
Section: Discussionmentioning
confidence: 95%
“…Enclosing the mycorrhizas within the rind of the tubercle may reduce such contact to rhizomorphs or mycelial cords which connect the tuberculate ectomycorrhizas with mycelial fans in the soil (Trappe, 1965). Zak (1971) has suggested that the tubercles may protect the mycorrhizas from attack by pathogens and sap-sucking insects.…”
Section: Discussionmentioning
confidence: 99%